2013
DOI: 10.1371/journal.pone.0073075
|View full text |Cite
|
Sign up to set email alerts
|

A Second Tubulin Binding Site on the Kinesin-13 Motor Head Domain Is Important during Mitosis

Abstract: Kinesin-13s are microtubule (MT) depolymerases different from most other kinesins that move along MTs. Like other kinesins, they have a motor or head domain (HD) containing a tubulin and an ATP binding site. Interestingly, kinesin-13s have an additional binding site (Kin-Tub-2) on the opposite side of the HD that contains several family conserved positively charged residues. The role of this site in kinesin-13 function is not clear. To address this issue, we investigated the in-vitro and in-vivo effects of mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…With improved coverage, we observed that MCAK is strongly stabilized when captured in an intermediate state of depolymerization. This is consistent with a two-site tubulin binding mode previously reported (Zhang et al, 2013). Our analysis also supports an outwardly curving protofilament geometry: the tubulin surface normally within the lumen of a microtubule is now exposed (Figure 5B).…”
Section: Resultssupporting
confidence: 93%
“…With improved coverage, we observed that MCAK is strongly stabilized when captured in an intermediate state of depolymerization. This is consistent with a two-site tubulin binding mode previously reported (Zhang et al, 2013). Our analysis also supports an outwardly curving protofilament geometry: the tubulin surface normally within the lumen of a microtubule is now exposed (Figure 5B).…”
Section: Resultssupporting
confidence: 93%
“…This behavior of the Ska1 MTBD is strikingly similar to that observed for the kinesin-13 MCAK, which also induces the formation of a protofilament-like structure encircling microtubules [46]. In the case of both Ska1 and MCAK, it is unlikely that such a spiral or ring-like assembly is formed in cells (as occurs for the fungal Dam1 complex, for example [7, 8]).…”
Section: Resultssupporting
confidence: 64%
“…While both kinesin-8s and kinesin-13s also bind microtubules outside of their canonical motor domains, these kinesins still require ATP hydrolysis to affect microtubule dynamics. The secondary microtubule binding site of kinesin-13 is nucleotide-independent, but this kinesin still utilizes the hydrolysis of ATP to destabilize microtubules (Zhang et al, 2013), while the kinesin-8 Kip3 can either stabilize or destabilize microtubules through discrete binding sites in the motor domain (Fukuda et al, 2014; Su et al, 2011). In contrast, the C-terminal dependent tethering of KIF21B to microtubules is completely sufficient for regulation of dynamic instability, independent of motor function or ATP hydrolysis.…”
Section: Discussionmentioning
confidence: 99%